2014
DOI: 10.1080/09297049.2014.934216
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in decision making under risk: The role of executive functions and reasoning abilities in 8- to 19-year-old decision makers

Abstract: Previous studies have shown that children and adolescents often tend toward risky decisions despite explicit knowledge about the potential negative consequences. This phenomenon has been suggested to be associated with the immaturity of brain areas involved in cognitive control functions. Particularly, "frontal lobe functions," such as executive functions and reasoning, mature until young adulthood and are thought to be involved in age-related changes in decision making under explicit risk conditions. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 87 publications
2
13
0
Order By: Relevance
“…2 Risky behaviors in adolescents, such as fighting, acting without thinking, and engagement in risky behavior, have been negatively associated with performance-based executive function domains including working memory and decision-making abilities. 6,9,10 Related to driving, Mäntylä, Karlsson, Marklund 2 found that poor performance on updating tasks (i.e. working memory tasks), but not shifting or inhibition measures, predicted poor simulated driving performance in healthy, adolescent drivers.…”
mentioning
confidence: 99%
“…2 Risky behaviors in adolescents, such as fighting, acting without thinking, and engagement in risky behavior, have been negatively associated with performance-based executive function domains including working memory and decision-making abilities. 6,9,10 Related to driving, Mäntylä, Karlsson, Marklund 2 found that poor performance on updating tasks (i.e. working memory tasks), but not shifting or inhibition measures, predicted poor simulated driving performance in healthy, adolescent drivers.…”
mentioning
confidence: 99%
“…Results in the SCDT showed that percentage of risk elections remained stable around 35%, with decision times diminishing with age probably due to improvements in executive functioning that facilitated the decision-making process (Schiebener et al, 2014). There was also evidence that women are more risk-averse than men since they spent more decision time for the risky option, though they engage in risk behaviors at levels similar to men (Bohlin & Erlandsson, 2007;Van Leijenhorst et al, 2008).…”
Section: Discussionmentioning
confidence: 81%
“…The relationship between executive functioning and risky decision-making was explored in an experiment with 112 children and adolescents aged 8-19, who completed the Game of Dice Task (GDT) used to assess risky decision-making [43]. Participants also performed the Modified Card Sorting Test (MCST) to investigate executive function and the Ravens Progressive Matrices to assess reasoning.…”
Section: Neurobiological Considerationsmentioning
confidence: 99%